Analisis Kinerja Karyawan Terhadap Pendapatan di CV. Goodspeed Coffee Bitung - Devie Mathilda Lumentut; Carolin Felisitas Telah (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This study aims to analyze the efforts made by the management of CV Goodspeed Coffee Bitung to improve employee performance and company revenue, as well as to identify the factors influencing employee performance. Additionally, this research examines the impact of employee performance on customer satisfaction and loyalty. A qualitative approach was used to gather in-depth information through interviews, observations, and documentation. The findings show that CV Goodspeed Coffee's management has implemented strategies such as setting clear work targets and conducting regular training to improve employee performance. Factors influencing employee performance include work discipline, skills, and positive attitudes. Good employee performance has been shown to have a positive impact on customer satisfaction and loyalty, which in turn increases the company's revenue. This study is expected to contribute theoretically to the development of human resource management and provide practical benefits for the company, academia, and the author for further development in the field of employee performance management.